2018
DOI: 10.18632/oncotarget.25549
|View full text |Cite
|
Sign up to set email alerts
|

In silico-designed mutations increase variable new-antigen receptor single-domain antibodies for VEGF165 neutralization

Abstract: The stability, binding, and tissue penetration of variable new-antigen receptor (VNAR) single-domain antibodies have been tested as part of an investigation into their ability to serve as novel therapeutics. V13 is a VNAR that recognizes vascular endothelial growth factor 165 (VEGF165). In the present study V13 was used as a parental molecule into which we introduced mutations designed in silico. Two of the designed VNAR mutants were expressed, and their ability to recognize VEGF165 was assessed in vitro and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…The in vitro anti-angiogenic effect of VS1-20 and VS0-4 was evaluated and results suggest that these antibodies are capable of inhibiting angiogenesis in a three-dimensional model based on endothelial cell spheroids. In silico analysis of anti-VEGF antibodies showed that vNARs from synthetic libraries could rival vNARs whose affinity had been improved through in silico modeling, with in vitro and in vivo anti-angiogenic effect previously reported [24]. This study also presents the first report of the construction of synthetic libraries of vNAR domains, using frameworks with three different number of Cys at their CDR3.…”
Section: Introductionsupporting
confidence: 51%
See 4 more Smart Citations
“…The in vitro anti-angiogenic effect of VS1-20 and VS0-4 was evaluated and results suggest that these antibodies are capable of inhibiting angiogenesis in a three-dimensional model based on endothelial cell spheroids. In silico analysis of anti-VEGF antibodies showed that vNARs from synthetic libraries could rival vNARs whose affinity had been improved through in silico modeling, with in vitro and in vivo anti-angiogenic effect previously reported [24]. This study also presents the first report of the construction of synthetic libraries of vNAR domains, using frameworks with three different number of Cys at their CDR3.…”
Section: Introductionsupporting
confidence: 51%
“…Docking, protein-protein affinity and interaction surface predictions of anti-VEGF antibodies, suggested that VS1-20 and VS0-4 recognize different epitopes, whereas VS1-20 and V13_P98Y recognize very close epitopes in the target molecule. The In silico analysis suggested that VS1-20 has a greater interaction with VEGF than VS0-4 and even than the control antibody V13_P98Y, an in silico maturated antibody with an in vitro and in vivo anti-angiogenic effect previously reported [24]. The results of the in silico analysis were supported by a competitive ELISA, it was evaluated if VS1-20 and V13_P98Y have an overlapping epitope and could block the union each other to VEGF.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations